STUDI POTENSI OBJEK DAN DAYA TARIK WISATA ALAM AIR TERJUN WIYONO DI TAMAN HUTAN RAYA WAN ABDUL RAHMAN, PROVINSI LAMPUNG - Rusita Rusita; Rahmat Walimbo; Yunita Sari; Melda Yanti (INFO-TEKNIK, 2016)
Wan Abdul Rachman Great Forest Park (Tahura WAR) is one of conservation forests in Lampung Province which has a variety of natural tourism potential that can be offered, one of which is Wiyono Waterfall. Tahura WAR became one of the targets the development of natural resource development Local governments (LGs) as stipulated in the law No. 10 in 2011 as a natural tourist destination in Lampung Province. The study was conducted in December 2015, aims to determine the potential of potential objects and natural tourist attraction (ODTWA) Wiyono Waterfall in Tahura WAR. The research uses a method of identification of potential tourism products and landscapes with scoring. While the data of flora, fauna, and the carrying capacity of the research that has been done Walimbo 2015. The results showed that ODTWA in part on top of Wiyono Waterfall included in a high quality product while part down of Wiyono Waterfall included in the category of medium quality, diversity of flora and fauna include  category of good, quality landscaping part on top of WiyonoWaterfall included in classes A and part down of Wiyono Waterfall belonging to class B, as well as the carrying capacity of tourist area Wiyono Waterfall Top and bottom covers carrying capacity of physical activity of picnic and camping each as much as 759 people per day and 122 people per day, ecological carrying capacity for the activity of picnic and camping each as much as 248 people per day and 165 people per day, the carrying capacity of the real to the activity of a picnic as many as 51 people per day and for the activity of camping as much as 9 per day.